Assessment of the Carbonate Rocks of the Pila Spi Formation for Cement Industry, in Permam Mountain, Erbil, Iraqi Kurdistan Region - Varoujan K. Sissakian; Dalyia A. Hamoodi; Hassan O. Omer; Sazan A. Nyazi (UKH Journal of Science and Engineering, 2019)
The Pila Spi Formation is exposed in Permam Mountain forming its carapace, and continuous ridges for few hundreds of kilometers. The rocks of the formation are mainly dolomitic limestone, dolomite, and limestone with various proportions. The thickness of the formation in Permam Mountain is about 100 m. Nine samples are collected from the Pila Spi Formation along a recently road cut across Permam Mountain. The sampling interval varies from 10 to 15 m. The collected samples were subjected to X-ray fluorescence (XRF) spectroscopy test to indicate the percentages of the main oxides in the samples. The results showed that the chemical composition of samples No. 1 and 9 meet the Iraqi standards for cement industry, whereas the remaining samples (Nos. 2–8) do not meet the Iraqi standards, and their total thickness is 80 m. To evaluate the suitability of the exposed rocks for cement industry in the sampled section within the Pila Spi Formation, different ratios of sample No. 1 were mixed with different ratios of a sample called sample No. A, it represents a mixture of samples No. 2–8. The mixing ratios are: (Sample No. 1/sample No. A) 50/50, 60/40, 70/30, 80/20, and 90/10. The same procedure was repeated for Sample No. 9. Another attempt was performed by mixing equal ratios of samples Nos. 1 and 9 with the same performed ratios with sample No. A.The chemical compositions of the samples were indicated using XRF test. The results showed that the best mixing ratios for the cement industry are 90:10, 80:20, and 70: 30 (samples Nos. 1+9: sample No. A).